2006
DOI: 10.1007/s10529-006-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Poplar Chitinase in Tomato Leads to Inhibition of Development in Colorado Potato Beetle

Abstract: The previously described poplar chitinase, WIN6, is induced during infestation by gypsy moth (Lymantria dispar L.) larvae, thus suggesting a role in defense against insect pests. To test this hypothesis, we produced tomato seedlings infected with a recombinant potato virus X (PVX), which produces WIN6, and tested its insecticidal properties on Colorado potato beetle [CPB; Leptinotarsa decemlineata (Say)], which is a serious pest of tomatoes and other crops. The advantage of PVX is that plant material is ready … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 22 publications
0
58
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8] Many chitinases have been expressed in various plants to enhance resistance against fungal disease, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and also resistance to spiders and insects. [20][21][22] When a powerful fungal endochitinase from a mycoparasitic fungus, Trichoderma, was expressed, the transgenic plants showed high resistance to a broad spectrum of fungal pathogens. [10][11][12]14,15) However, it was frequently found that expressing a single chitinase gene enhanced resistance only against a limited number of pathogens and/or to an inadequate level in transgenic plants, [3][4][5][6][7] which is probably to be attributed to the low chitinolytic and antifungal activities of the chitinases in question.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Many chitinases have been expressed in various plants to enhance resistance against fungal disease, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and also resistance to spiders and insects. [20][21][22] When a powerful fungal endochitinase from a mycoparasitic fungus, Trichoderma, was expressed, the transgenic plants showed high resistance to a broad spectrum of fungal pathogens. [10][11][12]14,15) However, it was frequently found that expressing a single chitinase gene enhanced resistance only against a limited number of pathogens and/or to an inadequate level in transgenic plants, [3][4][5][6][7] which is probably to be attributed to the low chitinolytic and antifungal activities of the chitinases in question.…”
mentioning
confidence: 99%
“…This indicates that the conversion of absorbed nutrients into caterpillar biomass was the lowest for those O. antiqua larvae fed leaves with a high chitinase expression. Some earlier studies show that transgenic chitinase may have a strong effect on insect growth and development (Regev et al, 1996;Lawrence & Novak, 2006;Corrado et al, 2008). The transgenic chitinase may affect lepidopteran larvae directly by damaging the peritrophic membrane (PM) lining the gut of insects (Kramer & Muthukrishnan, 1997;Lawrence & Novak, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies show that transgenic chitinase may have a strong effect on insect growth and development (Regev et al, 1996;Lawrence & Novak, 2006;Corrado et al, 2008). The transgenic chitinase may affect lepidopteran larvae directly by damaging the peritrophic membrane (PM) lining the gut of insects (Kramer & Muthukrishnan, 1997;Lawrence & Novak, 2006). Insect growth and development is very dependent on their capability of quickly remodelling the chitinous structures in peritrophic matrices just before moulting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L.) (Zvereva and Kozlov 1996), cucumber beetle (Diabrotica balteata LeConte) on lettuce (Lactuca sativa L.) (Huang et al 2003a), other chrysomelid beetles on corn (Zea mays L.) (Risch 1985) and Colorado potato beetle on tomato (Lycopersicon esculentum Mill.) (Lawrence and Novak 2006).…”
mentioning
confidence: 99%